$S^1$-bott functions on manifolds - Repovš, D.; Sharko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study $S^1$$ -Bott functions on compact smooth manifolds. In particular, we investigate $S_1$-invariant Bott functions on manifolds with circle action.